Technological innovation in Small and Medium Enterprises: A bibliometric analysis - Budianto, Roni; Praptapa, Agung; Herwiyanti, Eliada; Puji, Puji; Suyono, Eko; Rusmana, Oman (Goodwood Publishing, 2022)
Purpose: The objective of this study is to find out the development of SMEs in the digital era. Research Methodology: The authors used the Scopus database and searched for articles containing keywords such as